User perception on Mobile Augmented Reality as a marketing tool - Irshad, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Advancement in mobile information technology and the rapid growth of Internet over the past decade have substantially changed the end-user interacting environment. Therefore, it is appropriate to review the measures of user perception with latest information systems technology, especially in a mobile-based augmented reality environment, that has completely revolutionized the way of accessing and interacting with information thus invoking new experiences for users all around the world. The objective of this research is to investigate the perceived user perception of Mobile Augmented Reality (MAR). The results of this study show a remarkable positive perception of respondents regarding MAR in advertisement and marketing. Â© 2016 IEEE.